Factors Associated with Job Satisfaction and Self-Efficacy Among Nurses in Community Health Centers: A Cross-Sectional Study in Tanjungpinang City - Nur Meity Sulistia Ayu; Zuraidah; Tri Arianingsih; Ernawati; Tri Arianingsih (Caring: Indonesian Journal of Nursing Science, 2026)
Low levels of nurse’s job satisfaction and self-efficacy may reduce productivity, increase occupational stress, compromise the quality of patient care, and contribute to turnover intention. Identifying factors associated with job satisfaction and self-efficacy is therefore essential for strengthening nursing workforce management and improving healthcare outcomes. This study aimed to examine factors associated with job satisfaction and self-efficacy among nurses working in community health centers in Tanjungpinang City. A quantitative cross-sectional study was conducted among 92 nurses selected from a population of 120 using proportionate stratified random sampling based on the Slovin formula with a 5% margin of error. Data were collected using validated structured questionnaires and analyzed using Spearman’s rank correlation test. Among the 92 respondents, 70 (76.1%) reported high job satisfaction, while 67 (72.8%) demonstrated high self-efficacy. Interpersonal relationships (p < 0.001, r = 0.670) and social support (p = 0.001, r = 0.550) were significantly associated with job satisfaction, whereas workload was not significantly associated with job satisfaction (p = 0.904, r = −0.022). Verbal persuasion (p = 0.009, r = 0.447) and personal experience (p < 0.001, r = 0.690) were significantly associated with nurses’ self-efficacy. Organizational and psychological resources play a crucial role in enhancing nurses’ job satisfaction and self-efficacy. Nursing managers should prioritize evidence-based human resource management strategies that strengthen organizational support, enhance positive interpersonal relationships, expand mentoring and constructive feedback mechanisms, and promote continuous competency-based professional development to improve nurses’ performance. Keyword: Job Satisfaction, Self-efficacy, Nurses, Community Health Centers